2009
DOI: 10.1086/605028
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of Hospitalizations for Acute Gastroenteritis at 2 Sentinel Hospitals in Central Japan to Estimate the Health Burden of Rotavirus

Abstract: The burden of severe rotavirus disease among Japanese children is substantial and warrants consideration of vaccination as a prevention strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 10 publications
6
40
0
Order By: Relevance
“…The RESG has conducted a retrospective study (2003)(2004)(2005)(2006)(2007)) and a prospective active surveillance study (2008)(2009)) among inpatients with RV gastroenteritis in Mie Prefecture, Japan. The results of these studies have shown that the disease burden of hospitalization for RV gastroenteritis in Japan is comparable to that of other developed countries (8,9). Our group has continued to conduct studies on RV vaccine efficacy and cost-effectiveness with respect to the introduction of RV vaccines into the national immunization program.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…The RESG has conducted a retrospective study (2003)(2004)(2005)(2006)(2007)) and a prospective active surveillance study (2008)(2009)) among inpatients with RV gastroenteritis in Mie Prefecture, Japan. The results of these studies have shown that the disease burden of hospitalization for RV gastroenteritis in Japan is comparable to that of other developed countries (8,9). Our group has continued to conduct studies on RV vaccine efficacy and cost-effectiveness with respect to the introduction of RV vaccines into the national immunization program.…”
Section: Introductionmentioning
confidence: 73%
“…RV genotypes were determined using reverse transcription-polymerase chain reaction. In Tsu City, G3P [8] was dominant (61.0-77.1 ) before vaccine introduction, but decreased after introduction. Meanwhile, in an inverse proportion to the decrease in G3P [8], G1P [8] increased until the 2013 14 season, when a sudden predominance of G2P [4] (100 ) occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like influenza, RVGE is a seasonal disease that mainly occurs in the winter season, with a peak between February and March in Japan (7). Several hospital-based studies have reported on the incidence of RVGE among children aged º5 years; this incidence ranges from a minimum of 3.1 per 1,000 person-years to a maximum of 12.7 per 1,000 person-years (8)(9)(10). These local incidences were extrapolated to determine the annual number of rotavirus-associated hospitalizations, which was estimated to be 26,000-78,000 (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%